Phonological status of interdental phones [n], [l] and [t] in the Mapudungun spoken in the coastal area, Budi, Araucanía Region, Chile (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article deals with the phonetic-phonological status of the interdental consonants [n], [l] and [t], in the Mapudungun spoken in the Coastal area of the Huapi Island, IX Region of Araucania.  After analyzing minimal pairs, quantification of interdental segments versus alveolar [n], [l] and [t], and the phonological awareness of the assessed speakers, the validity of these segments could be concluded both as phones and as phonemes. That is to say, /n/, /l/ y /t/; y /n/, / l /and /t/, are phonemes in this area.
Keywords: Phonemes of the Mapudungun; Lafkenche; interdental consonants; phonology